2021
DOI: 10.3171/2020.11.jns203739
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes associated with brain tissue oxygen monitoring in patients with severe traumatic brain injury undergoing intracranial pressure monitoring

Abstract: OBJECTIVE Brain tissue oxygen monitoring combined with intracranial pressure (ICP) monitoring in patients with severe traumatic brain injury (sTBI) may confer better outcomes than ICP monitoring alone. The authors sought to investigate this using a national database. METHODS The National Trauma Data Bank from 2013 to 2017 was queried to identify patients with sTBI who had an external ventricular drain or intraparenchymal ICP monitor placed. Patients were stratified according to the placement of an intraparen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…18 In addition, many adult studies measure outcome by examining mortality rate or discharge location. 14,16,18 These outcomes were not as apparent in our study: for example, there were only 3 deaths and only 2 patients were discharged to another institution. Another difference between our results and findings compared to the adult population is the inherent difference in children recovery patterns.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…18 In addition, many adult studies measure outcome by examining mortality rate or discharge location. 14,16,18 These outcomes were not as apparent in our study: for example, there were only 3 deaths and only 2 patients were discharged to another institution. Another difference between our results and findings compared to the adult population is the inherent difference in children recovery patterns.…”
Section: Discussionmentioning
confidence: 54%
“…Although these correlations became insignificant after controlling for age and sex, these trends aligned with a recent study in the adult severe TBI population that found significantly increased ICU LOS and duration of mechanical ventilation in patients receiving ICP + PbtO 2 monitoring, compared to patients receiving only ICP monitoring. 14 Despite the increased LOS and mechanical ventilation period, which could be due to adverse effects from the treatments for cerebral hypoxia, the ICP + PbtO 2 group demonstrated lower mortality than the ICPonly group. 14 In a phase 2 safety and feasibility BOOST-II trial for adult severe TBI, a reduction in cerebral hypoxia time and a trend toward lower mortality and improved GOS-E outcome at 6 months were demonstrated in the ICP + PbtO 2 treatment group compared with the ICP-only treatment group.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1), and time spent above this threshold within the first 72 h post TBI has been shown to be associated with poor outcome [ ]. Recent data suggest a survival benefit in severe TBI patients when PbtO 2 and ICP monitoring are combined as compared with ICP monitoring alone [2], and consensus guidelines for their use have recently been published [15 & ]. Pathophysiological heterogeneity predicates the need for physiological imaging, and while both computed tomography and MRI can provide perfusion imaging, the gold standard technique for understanding cerebral metabolic derangements is PET.…”
Section: Key Pointsmentioning
confidence: 99%